Resin composition, and resin film, laminated film, and coating material using the same

JP7631739B2Active Publication Date: 2025-02-19MITSUBISHI CHEM CORP
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2020185233
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-11-05
Publication Date
2025-02-19
Estimated Expiration
2040-11-05

AI Technical Summary

Benefits of technology

【0015】 本発明によれば、加飾成型性、耐摩耗性及び耐候性に優れる樹脂フィルム、積層フィルム及び被覆材、並びに、耐摩耗性及び耐候性に優れ、前記樹脂フィルム、積層フィルム及び前記被覆材を製造可能な樹脂組成物を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007631739000001
    Figure 0007631739000001
  • Figure 0007631739000002
    Figure 0007631739000002
  • Figure 0007631739000003
    Figure 0007631739000003
Patent Text Reader

Abstract

To provide: a resin film, a laminated film and a coating material excellent in decorative moldability, wear resistance and weatherability; and a resin composition excellent in wear resistance and weatherability and capable of producing the resin film, a laminated film and the coating material.SOLUTION: There is provided a resin composition which comprises a thermoplastic polyurethane having an aliphatic diisocyanate component and a hardness of 90 A or more and a lubricant.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition, and a resin film, a laminated film, and a covering material each using the same. [Background technology]

[0002] 2. Description of the Related Art Conventionally, techniques for protecting the surfaces of various molded articles have been studied in various fields. For example, Patent Document 1 discloses an active energy ray-curable resin composition comprising a polyurethane resin (C) having a (meth)acryloyl group equivalent of 150 to 300 g / eq and an elongation of 50 to 400%, and a photopolymerization initiator (D). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2010-053357 A Summary of the Invention [Problem to be solved by the invention]

[0004] In Patent Document 1, the active energy ray curable resin composition is applied to the surface of a substrate, and then the substrate is irradiated with active energy rays to produce a coating having a hardened film. In this way, when a curable coating is provided on the surface of the substrate, the tensile elongation of the coating may be small when the coating is heated, or delamination may occur between the cured film and the substrate when the coating is stretched, so that the coating may not be suitable for decorative molding involving thermoforming, stretching, etc. Furthermore, in applications where the materials are exposed to a humid and hot environment, such as the exterior of vehicles and building materials, and the top sheets of home appliances, and where a long service life is required, coating materials that are not only abrasion resistant but also weather resistant are required.

[0005] The present invention aims to provide a resin film, a laminate film, and a covering material that are excellent in decorative moldability, abrasion resistance, and weather resistance, as well as a resin composition that is excellent in abrasion resistance and weather resistance and can be used to produce the resin film, the laminate film, and the covering material, and an object of the present invention is to achieve this objective. [Means for solving the problem]

[0006] In view of the above circumstances, the present inventors have conducted intensive research and have found that the above-mentioned problems can be solved, thereby completing the present invention.

[0007] <1> A resin composition containing a thermoplastic polyurethane having an aliphatic diisocyanate component and a hardness of 90A or more, and a lubricant.

[0008] <2> The lubricant comprises one or more selected from the group consisting of fatty acid amides and fatty acid esters. <1> The resin composition according to claim 1. <3> The content of the lubricant is 0.01 to 2.0 parts by mass relative to 100 parts by mass of the thermoplastic polyurethane. <1> or <2> 10. The resin composition according to claim 9 .

[0009] <4> The glass transition temperature of the thermoplastic polyurethane is 30° C. or less. <1> ~ <3> 10. The resin composition according to claim 9 . <5> The melt flow rate of the thermoplastic polyurethane at 220°C is 0.1 g / 10 min or more. <1> ~ <4> 10. The resin composition according to claim 9 . <6> The thermoplastic polyurethane includes at least one selected from the group consisting of polycarbonate type, polycaprolactone type, and polyester type. <1> ~ <5> 10. The resin composition according to claim 9 .

[0010] <7> The melting point of the lubricant is 25° C. or higher. <1> ~ <6> 10. The resin composition according to claim 9 .

[0011] <8> <1> ~ <7> 2. A resin film comprising the resin composition according to claim 1, having a dynamic friction coefficient of 0.450 or less. <9> <1> ~ <7> 2. A resin film comprising the resin composition according to claim 1, and having a tensile elongation at 150° C. of 100% or more.

[0012] <10> <8> or <9> A coating material using the resin film described in claim 1.

[0013] <11> <1> ~ <7> 1. A laminated film having a layer made of the resin composition according to any one of 1 to 8, and a substrate layer. <12> The layer made of the resin composition has a thickness of 3 to 200 μm. <11> The laminated film according to claim 1. <13> Tensile elongation at 150℃ is 100% or more <11> or <12> The laminated film according to claim 1.

[0014] <11> ~ <13> A covering material using the laminate film described in any one of the above. Effect of the Invention

[0015] According to the present invention, it is possible to provide a resin film, a laminate film, and a coating material that are excellent in decorative moldability, abrasion resistance, and weather resistance, as well as a resin composition that is excellent in abrasion resistance and weather resistance and can be used to produce the resin film, the laminate film, and the coating material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] Hereinafter, an embodiment of the present invention will be described in detail. However, the content of the present invention is not limited to the embodiment described below.

[0017] <Resin composition> The resin composition of the present invention contains a thermoplastic polyurethane having an aliphatic diisocyanate component and a hardness of 90A or more, and a lubricant. The resin composition of the present invention may further contain additives such as a colorant and an ultraviolet absorber. The resin composition of the present invention is excellent in abrasion resistance and weather resistance, and can be used to produce resin films, laminated films, and covering materials that are excellent in decorative moldability, abrasion resistance, and weather resistance. In the present invention, "weather resistance" refers to the fact that bleeding of the lubricant does not occur and that there is no significant decrease in transparency and abrasion resistance even when stored in a humid and hot environment (hereinafter also referred to as "humid and heat resistance"). More preferably, in addition to the above-mentioned humid and heat resistance, it refers to the fact that the film is not easily yellowed even when irradiated with ultraviolet rays (hereinafter also referred to as "yellowing resistance").

[0018] The resin composition of the present invention has good abrasion resistance because it contains a thermoplastic polyurethane having a hardness of 90A or more and a lubricant. In addition, since the thermoplastic polyurethane of the present invention has a hardness of 90A or more, bleeding of the lubricant in a humid and hot environment can be suppressed, and therefore, even if a film made of the resin composition of the present invention is stored in a humid and hot environment, the transparency and abrasion resistance can be maintained. Furthermore, since the thermoplastic polyurethane of the present invention contains an aliphatic diisocyanate component, yellowing of the film can be suppressed. Furthermore, a film made of the resin composition of the present invention has a large tensile elongation when heated and can maintain its transparency even when stretched, and therefore has good decorative formability. The resin composition of the present invention, and the resin film, laminate film and covering material each using the same will be described in detail below.

[0019] [Thermoplastic polyurethane] The resin composition of the present invention contains a thermoplastic polyurethane having an aliphatic diisocyanate component and a hardness of 90A or more. Hereinafter, the "thermoplastic polyurethane having an aliphatic diisocyanate component and a hardness of 90A or more" may be referred to as the "polyurethane of the present invention." In the polyurethane of the present invention, "having an aliphatic diisocyanate component" means that an aliphatic diisocyanate is used as a raw material for the polyurethane, and the polyurethane molecule has a molecular skeleton derived from the aliphatic diisocyanate. The hardness of the polyurethane in the present invention means hardness A measured by a method in accordance with JIS K 7311-1995 (testing method for polyurethane thermoplastic elastomers).

[0020] Polyurethane is a general term for compounds that have a urethane bond (-NHCOO-) and are obtained by a polyaddition reaction (urethanization reaction) between isocyanate (-NCO) and alcohol (-OH). Thermoplastic polyurethane (TPU) includes polyurethane obtained by reaction of short-chain glycol (low molecular weight polyol) with isocyanate, polyurethane obtained by reaction of long-chain glycol (high molecular weight polyol) with isocyanate, etc., and the polyurethane in the present invention has an aliphatic diisocyanate as the isocyanate. Since the polyurethane in the present invention has a molecular skeleton derived from an aliphatic diisocyanate, the weather resistance of the resin composition is excellent. Examples of the aliphatic diisocyanate include hexamethylene diisocyanate, hydrogenated 4,4-diphenylmethane diisocyanate, 1,4-bis(isocyanatomethyl)cyclohexane, hydrogenated xylylene diisocyanate, lysine diisocyanate, and isophorone diisocyanate.

[0021] The polyurethane in the present invention may be a block copolymer having, as a hard segment, a structural unit derived from polyurethane, and, as a soft segment, a structural unit derived from polyether, polycarbonate, polycaprolactone, polyester, etc. The soft segment may be a single type or a combination of multiple types. Hereinafter, a block copolymer having a polyurethane-derived structural unit as a hard segment and a polyether-derived structural unit as a soft segment is referred to as a polyether-type polyurethane. A block copolymer having a polyurethane-derived structural unit as a hard segment and a polycarbonate-derived structural unit as a soft segment is called a polycarbonate-type polyurethane; A block copolymer having a polyurethane-derived structural unit as a hard segment and a polycaprolactone-derived structural unit as a soft segment is called a polycaprolactone-type polyurethane; A block copolymer having a polyurethane-derived structural unit as the hard segment and a polyester-derived structural unit as the soft segment is called a polyester-type polyurethane.

[0022] From the viewpoint of further improving hardness, the polyurethane in the present invention preferably contains one or more types selected from the group consisting of polycarbonate type, polycaprolactone type, and polyester type. From the viewpoint of low temperature characteristics, polyether type or polyester type is preferable, from the viewpoint of heat resistance, polycarbonate type or polycaprolactone type is preferable, and from the viewpoint of hydrolysis resistance, polycarbonate type is more preferable.

[0023] (hardness) The polyurethane in the present invention has a hardness of 90A or more. If the hardness of the polyurethane in the present invention is less than 90A, the abrasion resistance of the resin composition cannot be obtained. From the viewpoint of further improving the abrasion resistance of the resin composition, the hardness of the polyurethane in the present invention is preferably 93A or more, more preferably 95A or more, and even more preferably 96A or more. The upper limit of the hardness of the polyurethane in the present invention is not particularly limited, but from the viewpoint of easy availability as a general-purpose product, it is preferably 98A or less.

[0024] (glass transition temperature, melting point) The glass transition temperature (Tg) of the polyurethane in the present invention is preferably 30° C. or lower. By making the Tg of the polyurethane of the present invention 30° C. or less, the surface state is less likely to change in practical environments and abrasion resistance can be maintained. The Tg of the polyurethane of the present invention is more preferably 25° C. or less, and even more preferably 20° C. or less. The lower limit of the Tg of the polyurethane is not particularly limited, but from the viewpoint of easy availability as a general-purpose product, it is preferably −100° C. or higher. Furthermore, the polyurethane in the present invention does not need to have a melting point (Tm), but if it does have a melting point (Tm), it is preferably 60 to 200°C. When the Tm of the polyurethane in the present invention is 60° C. or higher, the heat resistance is good, and when it is 200° C. or lower, the film formability is good. The Tm of the polyurethane in the present invention is more preferably 70 to 195° C., and further preferably 75 to 190° C. The Tg and Tm of the polyurethane in the present invention can be measured by differential scanning calorimetry (DSC).

[0025] (Melt Flow Rate) The polyurethane of the present invention preferably has a melt flow rate (MFR) at 220° C. of 0.1 g / 10 min or more. When the MFR is 0.1 g / 10 min or more, the melt viscosity of the resin composition during molding is unlikely to become high, and productivity is excellent. From the viewpoint of film formability, the MFR of the polyurethane in the present invention is preferably 100 g / 10 min or less. The MFR of the polyurethane of the present invention at 220° C. is more preferably from 0.5 to 80 g / 10 min, and further preferably from 0.6 to 70 g / 10 min. The MFR is based on JIS K7210-1999 and is a value measured under conditions of a temperature of 220°C and a load of 2.16 kg.

[0026] The content of the polyurethane in the resin composition of the present invention is preferably 60 to 100 mass%, more preferably 70 to 99 mass%, and even more preferably 80 to 98 mass%, from the viewpoints of abrasion resistance, weather resistance, and decorative moldability.

[0027] [Lubricant] The resin composition of the present invention contains a lubricant. From the viewpoint of the decorative moldability of the resin film, laminated film and covering material obtained from the resin composition of the present invention, it is desirable for the lubricant to be uniformly dispersed in the resin composition.

[0028] The lubricant is not particularly limited as long as it is a material that can reduce friction between the surface of the resin composition of the present invention and a substance adjacent thereto. For example, hydrocarbons, fatty acids, fatty acid amides, fatty acid esters, alcohols, metal soaps, etc. may be mentioned. Only one type of lubricant may be used, or two or more types may be used in combination.

[0029] The melting point of the lubricant is preferably room temperature (25° C.) or higher, and more preferably higher than room temperature (25° C.), from the viewpoint of improving the dispersibility of the lubricant in the resin composition and suppressing blooming. The melting point of the lubricant is preferably 150° C. or lower. When the melting point of the lubricant is 150° C. or lower, the lubricant has excellent compatibility with the polyurethane of the present invention, and can improve the lubricity of the surface of the resin composition. The melting point of the lubricant is more preferably 140° C. or lower, and even more preferably 130° C. or lower.

[0030] Among the above, from the viewpoints of excellent compatibility with the polyurethane in the present invention and suppressing blooming from the surface of the resin composition, it is preferable that the lubricant contains one or more selected from the group consisting of fatty acid amides and fatty acid esters.

[0031] As the fatty acid amide, an amide of a fatty acid having 12 or more carbon atoms can be used, and specific examples thereof include stearylamide, palmitylamide, oleylamide, methylene bis stearoamide, and ethylene bis stearoamide.

[0032] As the fatty acid ester, an ester of a fatty acid having 12 or more carbon atoms can be used, and specific examples thereof include butyl stearate, hydrogenated castor oil, and ethylene glycol monostearate.

[0033] The content of the lubricant in the resin composition of the present invention is preferably 0.01 to 2.0 parts by mass relative to 100 parts by mass of the polyurethane of the present invention. When the content of the lubricant is 0.01 part by mass or more relative to 100 parts by mass of the polyurethane of the present invention, the lubrication of the surface of the resin composition is excellent, and when the content is 2.0 parts by mass or less, blooming from the surface of the resin composition can be suppressed. The content of the lubricant is more preferably 0.02 to 1.5 parts by mass, and even more preferably 0.03 to 1.0 part by mass, relative to 100 parts by mass of the polyurethane in the present invention.

[0034] The resin composition of the present invention may contain additives as optional components other than the polyurethane and the lubricant of the present invention. Examples of additives include colorants, flame retardants, antioxidants, ultraviolet absorbers, light stabilizers, conductive materials, antibacterial agents, etc. The additives may be used in amounts normally used. From the viewpoint of not impairing abrasion resistance and weather resistance, the resin composition of the present invention preferably comprises the polyurethane of the present invention and a lubricant.

[0035] The resin composition of the present invention preferably does not contain inorganic particles and / or organic particles as additives, or if it does contain them, the content is less than 5 parts by mass per 100 parts by mass of thermoplastic polyurethane. In other words, the content of one or more additives selected from the group consisting of inorganic particles and organic particles in the resin composition of the present invention is preferably 0 part by mass or more and less than 5 parts by mass per 100 parts by mass of thermoplastic polyurethane. Examples of inorganic particles include calcium carbonate, magnesium carbonate, barium carbonate, magnesium sulfate, barium sulfate, calcium sulfate, zinc oxide, magnesium oxide, calcium oxide, titanium oxide, aluminum oxide, zinc oxide, alumina, aluminum hydroxide, hydroxyapatite, silica, magnesium silicate, mica, talc, kaolin, clay, glass powder, asbestos powder, zeolite, and clay silicate. Examples of the organic particles include (meth)acrylate resin particles, styrene resin particles, silicone resin particles, nylon resin particles, polyethylene resin particles, benzoguanamine resin particles, and urethane resin particles. Among the above, the resin composition of the present invention preferably does not contain silica, or if it does contain silica, the content is less than 5 parts by mass per 100 parts by mass of thermoplastic polyurethane. By setting the content of silica within the above range, a film with good transparency can be obtained. In addition, the transparency when the film is stretched is also good, so that the decorative formability is further improved.

[0036] The resin composition of the present invention can be prepared by melt-kneading the polyurethane of the present invention, the lubricant, and any other components that may be included. By melt-kneading, the lubricant is easily dispersed uniformly in the resin composition, and when a resin film, a laminated film, or a covering material is produced from the resin composition of the present invention, the decorative moldability of the resin film, the laminated film, or the covering material is not easily impaired.

[0037] <Resin film> The resin composition of the present invention may be melt-kneaded and molded into a film. The resin film made of the resin composition of the present invention may be a single layer or two or more layers. From the viewpoint of maintaining abrasion resistance and weather resistance, the total thickness of the resin film is preferably from 3 to 200 μm, more preferably from 10 to 150 μm, and even more preferably from 20 to 120 μm.

[0038] (Light transmittance) From the viewpoint of transparency, the resin film of the present invention preferably has a light transmittance of 90% or more, and more preferably 91% or more. From the viewpoint of resistance to moist heat, the light transmittance after storage of the resin film for one month in an environment of 40° C. and 90% RH is preferably 90% or more, and more preferably 91% or more.

[0039] (Hayes) From the viewpoint of transparency, the resin film of the present invention preferably has a haze of 10% or less, more preferably 8% or less, and even more preferably 5% or less. From the viewpoint of resistance to moist heat, the haze of the resin film after storage for one month in an environment of 40°C and 90% RH is preferably 10% or less, more preferably 8% or less, and even more preferably 5% or less. Furthermore, the difference (Δhaze) between the haze after storing the resin film for one month in an environment of 40°C and 90% RH and the haze before storage is preferably within the range of ±3%, more preferably within the range of ±2%, and even more preferably within the range of ±1%.

[0040] (Kinematic friction coefficient) The resin film of the present invention preferably has a dynamic friction coefficient of 0.450 or less. When the resin film of the present invention has a dynamic friction coefficient of 0.450 or less, the abrasion resistance of the surface of the resin film is good. The dynamic friction coefficient of the resin film of the present invention is more preferably 0.440 or less, and even more preferably 0.430 or less. The dynamic friction coefficient of the resin film of the present invention is not particularly limited, but is usually 0.100 or more. The dynamic friction coefficient of the resin film of the present invention can be measured by a static and dynamic friction measuring device (manufactured by Traniity Labs).

[0041] From the viewpoint of decorative moldability, the resin film of the present invention has a tensile elongation at 150° C. of preferably 100% or more, more preferably 120% or more, and even more preferably 150% or more. The upper limit is not particularly limited, but is usually 500%. The tensile elongation of the resin film can be measured using a tensile tester according to a method in accordance with JIS K7161-1-2014.

[0042] <Laminated film> The laminate film of the present invention has a layer made of the resin composition of the present invention and a substrate layer. The laminated film of the present invention may further have an adhesive layer for bonding the layer made of the resin composition of the present invention to the substrate layer, a colored layer containing a colorant, and the like. The base layer is not particularly limited, but is preferably made of a material having a large tensile elongation, and preferably contains, for example, a thermoplastic resin, such as a polyolefin thermoplastic resin, a polystyrene thermoplastic resin, a polyamide thermoplastic resin, a polyester thermoplastic resin, or a polyurethane thermoplastic resin. For the substrate layer, it is preferable to use a rubber-containing acrylic resin composition (A) described below.

[0043] [Rubber-containing acrylic resin composition (A)] The rubber-containing acrylic resin composition (A) preferably has a bimodal tan δ peak temperature, with the low-temperature peak having a maximum value of less than 40° C. and the high-temperature peak having a maximum value of 40° C. or more, and more preferably has the low-temperature peak having a maximum value of less than 20° C. and the high-temperature peak having a maximum value of 60° C. or more. When the low-temperature peak has a maximum value of less than 40° C., flexibility at processing temperatures of less than 40° C. is improved. Also, when the high-temperature peak has a maximum value of 40° C. or more, this is advantageous from the viewpoint of processability during production. In the present invention, the tan δ peak temperature refers to the temperature at which tan δ at a frequency of 0.1 Hz shows a maximum value when a test piece (long side: 20 mm, short side: 6 mm, thickness: 100 μm) of the rubber-containing acrylic resin composition (A) is heated from -100°C to 150°C at a rate of 2°C / min in a nitrogen atmosphere using a dynamic viscoelasticity measuring device (product name "DMS6100", manufactured by SII Nano Technology Inc.).

[0044] Examples of the rubber-containing acrylic resin composition (A) include a rubber-containing acrylic resin composition, a graft copolymer, and a mixture thereof. From the viewpoint of productivity, the rubber-containing acrylic resin composition (A1) shown below is preferred.

[0045] [Rubber-containing acrylic resin composition (A1)] The rubber-containing acrylic resin composition (A1) may contain a core-shell rubber (A1-1), a thermoplastic polymer (A1-2), and an additive (C1). In particular, the rubber-containing acrylic resin composition (A1) preferably contains 5.5 to 99.9% by mass of (A1-1) and 0.1 to 94.5% by mass of (A1-2) relative to 100 parts by mass of the sum of (A1-1) and (A1-2), and further contains 0.1 to 20 parts by mass of additive (C1) relative to 100 parts by mass of the sum of (A1-1) and (A1-2). If the content of the core-shell rubber (A1-1) is 5.5% by mass or more, the substrate layer is provided with greater toughness, the laminated film is less likely to break during production, and the productivity is good. In addition, the laminated film has good handleability during use. The rubber-containing acrylic resin composition (A) preferably contains 10% by mass or more and 99.7% by mass or less of (A1-1) and 0.3% by mass or more and 90% by mass or less of (A1-2) relative to 100% by mass of the total of (A1-1) and (A1-2); and more preferably contains 15% by mass or more and 99.5% by mass or less of (A1-1) and 0.5% by mass or more and 85% by mass or less of (A1-2). The rubber-containing acrylic resin composition (A) preferably contains 0.5 to 10 parts by mass, and more preferably 1 to 8 parts by mass, of the additive (C1) per 100 parts by mass of the total of (A1-1) and (A1-2). The rubber-containing acrylic resin composition (A1) may not contain the thermoplastic polymer (A1-2) and the additive (C1).

[0046] [Core-shell rubber (A1-1)] The core-shell rubber (A1-1) is not particularly limited as long as it is a particle containing an acrylic resin. However, the core-shell rubber (A1-1) is preferably an acrylic rubber particle having a multi-layer structure of two or more layers, in which a layer containing a hard polymer (a-2) is formed as an outer layer on a layer containing an elastic copolymer (a-1) as an inner layer. In particular, the core-shell rubber (A1-1) is preferably an acrylic rubber particle having a multilayer structure of two or more layers, in which a layer containing a hard polymer (a-2) as an outer layer having a structure of one or more layers and obtained by graft polymerization of a monomer mainly composed of an alkyl methacrylate ester is formed on a layer containing an elastic copolymer (a-1) as an inner layer having a structure of one or more layers and obtained mainly from an alkyl methacrylate ester. In addition, the core-shell rubber (A1-1) may have one or more layers containing an intermediate polymer (a-3) between the layer containing the elastic copolymer (a-1) and the layer containing the hard polymer (a-2).

[0047] The content of the elastic copolymer (a-1) in the core-shell rubber (A1-1) is preferably from 5% by mass to 90% by mass, more preferably from 10% by mass to 70% by mass. The content of the hard polymer (a-2) in the core-shell rubber (A1-1) is preferably from 5% by mass to 90% by mass, and more preferably from 10% by mass to 70% by mass. The content of the intermediate polymer (a-3) in the core-shell rubber (A1-1) is preferably 0% by mass or more and 35% by mass or less, more preferably 0% by mass or more and 20% by mass or less. When the content is 35% by mass or less, the balance of the final polymer is good.

[0048] The elastic copolymer (a-1) is preferably a polymer obtained by polymerizing a monomer composition containing an alkyl acrylate. Here, (meth)acrylic acid refers to acrylic acid or methacrylic acid. The elastic copolymer (a-1) is more preferably a polymer obtained by polymerizing a monomer composition containing an alkyl acrylate. The monomer composition may further contain a monomer other than the (meth)acrylic acid alkyl ester and a crosslinkable monomer. For example, the elastic copolymer (a-1) may contain 80% by mass or more and 100% by mass or less of an acrylic acid alkyl ester having an alkyl group with 1 to 8 carbon atoms and a methacrylic acid alkyl ester having an alkyl group with 1 to 4 carbon atoms, 0% by mass or more and 20% by mass or less of a monomer other than the (meth)acrylic acid alkyl ester, and 0.01% by mass or more and 10% by mass or less of a crosslinkable monomer (total 100% by mass).

[0049] As the alkyl acrylate having an alkyl group having 1 to 8 carbon atoms, for example, methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, and n-octyl acrylate are preferable, and alkyl acrylates having a low Tg are more preferable. These may be used alone or in combination of two or more.

[0050] The acrylic acid alkyl ester is used as a main component of the monomer constituting the elastic copolymer (a-1). Specifically, the amount of the acrylic acid alkyl ester used is preferably 30% by mass or more and 99.9% by mass or less based on the total monomer constituting the elastic copolymer (a-1). When the amount used is 30% by mass or more, the moldability of the film is good. The amount used is more preferably 50% by mass or more and 95% by mass or less. In addition, the range of the amount used indicates the amount of the alkyl acrylate used in the elastic copolymer (a-1) as a whole when the elastic copolymer (a-1) has a structure of two or more layers. For example, when the elastic copolymer (a-1) is made into a hard core structure, the amount of the alkyl acrylate used in the first layer (core) can be less than 30 mass%.

[0051] Examples of methacrylic acid alkyl esters having an alkyl group having 1 to 4 carbon atoms include methyl methacrylate, ethyl methacrylate, propyl methacrylate, and butyl methacrylate. These may be used alone or in combination of two or more. The amount of methacrylic acid alkyl ester used is preferably 0% by mass or more and 69.9% by mass or less, more preferably 0% by mass or more and 40% by mass or less, based on the total monomers constituting the elastic copolymer (a-1).

[0052] Examples of the monomer other than the (meth)acrylic acid alkyl ester include other vinyl monomers copolymerizable with the (meth)acrylic acid alkyl ester. Examples of the monomer other than the (meth)acrylic acid alkyl ester include styrene and acrylonitrile. These may be used alone or in combination of two or more. When using a monomer other than the (meth)acrylic acid alkyl ester, the amount of the monomer used is preferably 0% by mass or more and 69.9% by mass or less, more preferably 0% by mass or more and 20% by mass or less, based on the total monomers constituting the elastic copolymer (a-1).

[0053] Examples of the crosslinkable monomer include ethylene glycol dimethacrylate, 1,3-butylene glycol dimethacrylate, 1,4-butylene glycol dimethacrylate, propylene glycol dimethacrylate, and a graft crosslinking agent. These may be used alone or in combination of two or more. The amount of the crosslinkable monomer used is preferably 0.1% by mass or more and 10% by mass or less, more preferably 0.5% by mass or more and 5% by mass or less, based on the total monomers constituting the elastic copolymer (a-1). In terms of the stability of the core-shell rubber (A1-1), it is preferable to use a graft crosslinking agent as the crosslinkable monomer.

[0054] Examples of the graft crosslinking agent include allyl esters, methallyl esters, or crotyl esters of α,β-unsaturated carboxylic acids or unsaturated dicarboxylic acids; triallyl cyanurate, triallyl isocyanurate, etc. Among these, allyl esters of acrylic acid, methacrylic acid, maleic acid, fumaric acid, etc. are preferred, and allyl methacrylate is more preferred because of its excellent effect. Such graft crossing agents mainly react and chemically bond with the conjugated unsaturated bond of the ester much faster than with the allyl, methallyl or crotyl groups. Most of the allyl, methallyl or crotyl groups, which react slowly, function effectively during the polymerization of the next layer polymer, providing graft bonds between two adjacent layers. Therefore, in order to suppress whitening during film deformation, it is preferable that layers other than the outermost layer contain at least 0.01% by mass of the graft crossing agent.

[0055] The rigid polymer (a-2) is preferably a polymer obtained by polymerizing a monomer other than an alkyl methacrylate ester, an alkyl acrylate ester, and an alkyl (meth)acrylate ester. For example, the rigid polymer (a-2) is obtained by polymerizing a monomer consisting of 51% by mass to 100% by mass of an alkyl methacrylate ester having an alkyl group with 1 to 4 carbon atoms and 0% by mass to 49% by mass of an alkyl acrylate ester having an alkyl group with 1 to 8 carbon atoms or a monomer other than an alkyl (meth)acrylate ester in the presence of an elastic copolymer (a-1). As the monomer other than an alkyl methacrylate ester having an alkyl group with 1 to 4 carbon atoms, an alkyl acrylate ester having an alkyl group with 1 to 8 carbon atoms, and an alkyl (meth)acrylate ester, the same monomer as that used for polymerization of the elastic copolymer (a-1) can be used.

[0056] The intermediate polymer (a-3) is preferably a polymer obtained by polymerizing a monomer composition containing an alkyl acrylate, an alkyl methacrylate, a monomer other than an alkyl (meth)acrylate, and a crosslinkable monomer. The intermediate polymer (a-3) is more preferably a polymer obtained by polymerizing a monomer composition containing an alkyl acrylate having an alkyl group with 1 to 8 carbon atoms, an alkyl methacrylate having an alkyl group with 1 to 4 carbon atoms, a monomer other than an alkyl (meth)acrylate, and a crosslinkable monomer. For example, the intermediate polymer (a-3) may contain 10% by mass or more and 90% by mass or less of an alkyl acrylate having an alkyl group with 1 to 8 carbon atoms, 90% by mass or more and 10% by mass or less of an alkyl methacrylate having an alkyl group with 1 to 4 carbon atoms, 0% by mass or more and 20% by mass or less of a monomer other than an alkyl (meth)acrylate, and 0.01% by mass or more and 10% by mass or less of a crosslinkable monomer (total 100% by mass).

[0057] The monomers used in the intermediate polymer (a-3) may be the same as those used in the polymerization of the elastic copolymer (a-1). The content (monomer composition ratio) of the alkyl acrylate in the intermediate polymer (a-3) is preferably lower than that in the elastic copolymer (a-1) and higher than that in the rigid polymer (a-2).

[0058] The average particle size of the core-shell rubber (A1-1) is preferably 0.01 μm or more and 0.5 μm or less, more preferably 0.08 μm or more and 0.3 μm or less. In particular, from the viewpoint of film-forming properties, the average particle size is preferably 0.08 μm or more. The average particle size is a value measured by the method described later.

[0059] The method for producing the core-shell rubber (A1-1) is not particularly limited. The elastic copolymer (a-1) and the rigid polymer (a-2) can be produced, for example, by emulsion polymerization. They can also be produced by emulsion suspension polymerization, which converts the emulsion polymerization into a suspension polymerization system when polymerizing the polymer constituting the outermost layer. The polymerization temperature is appropriately selected depending on the type and amount of the polymerization initiator used, and is preferably 40°C or higher and 120°C or lower, and more preferably 60°C or higher and 95°C or lower. As the polymerization initiator, a known polymerization initiator can be used. The polymerization initiator can be added to either the aqueous phase or the monomer phase, or both.

[0060] Examples of emulsifiers that can be used in emulsion polymerization include anionic, cationic, and nonionic surfactants, with anionic surfactants being preferred. Examples of anionic surfactants include carboxylate surfactants such as potassium oleate, sodium stearate, sodium myristate, sodium N-lauroyl sarcosinate, and dipotassium alkenyl succinate; sulfate ester surfactants such as sodium lauryl sulfate; sulfonate surfactants such as sodium dioctyl sulfosuccinate, sodium dodecylbenzenesulfonate, and sodium alkyl diphenyl ether disulfonate; and phosphate ester surfactants such as sodium polyoxyethylene alkyl phenyl ether phosphate. These may be used alone or in combination of two or more.

[0061] The polymer latex obtained by emulsion polymerization can be filtered, for example, with a filter having an opening of 100 μm or less, and then separated and recovered by a method such as an acid coagulation method, a salt coagulation method, a freeze coagulation method, or a spray drying method. In the acid coagulation method, an inorganic acid such as sulfuric acid, hydrochloric acid, or phosphoric acid, or an organic acid such as acetic acid can be used. In the salt coagulation method, an inorganic salt such as sodium sulfate, magnesium sulfate, aluminum sulfate, or calcium chloride, or an organic salt such as calcium acetate or magnesium acetate can be used. These may be used alone or in combination of two or more. The separated and recovered polymer is further washed, dehydrated, dried, or the like to obtain a core-shell rubber (A1-1).

[0062] [Thermoplastic polymer (A1-2)] The thermoplastic polymer (A1-2) is a thermoplastic polymer other than the core-shell rubber (A1-1), and is preferably a polymer obtained by polymerizing a monomer containing an alkyl methacrylate ester as a main component. Examples of the thermoplastic polymer (A1-2) include the thermoplastic polymers and polymer-based processing aids described in WO 2014 / 192708.

[0063] [Additive (C1)] The additive (C1) is a compound other than the core-shell rubber (A1-1) and the thermoplastic polymer (A1-2), and examples thereof include stabilizers, lubricants, processing aids, plasticizers, impact resistance improvers, foaming agents, fillers, colorants, ultraviolet absorbers, and antiblocking agents.

[0064] For example, from the viewpoint of imparting weather resistance, it is preferable to contain an ultraviolet absorber as the additive (C1). The molecular weight of the ultraviolet absorbent is preferably 300 or more, more preferably 400 or more. When the molecular weight is 300 or more, the ultraviolet absorbent is less likely to volatilize during vacuum molding or pressure molding in an injection mold, and mold staining is less likely to occur. The type of ultraviolet absorbent is not particularly limited, but a benzotriazole-based ultraviolet absorbent having a molecular weight of 400 or more and a triazine-based ultraviolet absorbent having a molecular weight of 400 or more are preferred.

[0065] As a benzotriazole-based ultraviolet absorber having a molecular weight of 400 or more, commercially available products include, for example, "TV234" (trade name, manufactured by BASF) and "Adeka STAB LA-31RG" (trade name, manufactured by ADEKA Corporation). As a triazine-based ultraviolet absorber having a molecular weight of 400 or more, commercially available products include, for example, "TV1577" (trade name, manufactured by BASF). These may be used alone or in combination of two or more. From the viewpoint of weather resistance, the amount of the ultraviolet absorber to be added is preferably 0 to 20 parts by mass, more preferably 1 to 5 parts by mass, based on 100 parts by mass of the total of the core-shell rubber (A1-1) and the thermoplastic polymer (A1-2).

[0066] In addition, from the viewpoint of further improving weather resistance, it is preferable to use a radical scavenger such as a hindered amine-based light stabilizer in combination with the ultraviolet absorber. Commercially available radical scavengers include, for example, "ADK STAB LA-57", "ADK STAB LA-62", "ADK STAB LA-67", "ADK STAB LA-63", and "ADK STAB LA-68" (all trade names, manufactured by ADEKA CORPORATION); "SANOL LS-770", "SANOL LS-765", "SANOL LS-292", "SANOL LS-2626", "SANOL LS-1114", and "SANOL LS-744" (all trade names, manufactured by Sankyo Lifetech Co., Ltd.). These may be used alone or in combination of two or more kinds. From the viewpoint of bleed-out resistance, the amount of the radical scavenger added is preferably 0 parts by mass or more and 10 parts by mass or less, and more preferably 0.2 parts by mass or more and 5 parts by mass or less, per 100 parts by mass of the total of the core-shell rubber (A1-1) and the thermoplastic polymer (A1-2).

[0067] In addition, from the viewpoint of preventing adhesion to a press plate when a laminate is produced by pressing, the additive (C1) is preferably a release agent. Examples of the release agent include silicone compounds, fluorine compounds, aliphatic alcohols, and aliphatic carboxylic acids. Among these, alkyl carboxylic acids are preferred from the standpoint of availability and economy. Examples of the aliphatic carboxylic acid used as a release agent include linoleic acid, vaccenic acid, stearic acid, oleic acid, margaric acid, palmitoleic acid, palmitic acid, and pentadecylic acid. These may be used alone or in combination of two or more.

[0068] From the viewpoint of viscosity adjustment, the additive (C1) is preferably a plasticizer. From the viewpoint of bleed-out resistance, the amount of the plasticizer added is preferably 0 to 9 parts by mass, more preferably 0 to 5 parts by mass, based on 100 parts by mass of the core-shell rubber (A1-1) and the thermoplastic polymer (A1-2) in total.

[0069] Examples of the plasticizer include phthalates such as di-n-butyl phthalate, di-n-octyl phthalate, bis(2-ethylhexyl) phthalate, di-n-decyl phthalate, and diisodecyl phthalate; adipates such as bis(2-ethylhexyl) adipate and di-n-octyl adipate; sebacates such as bis(2-ethylhexyl) sebacate and di-n-butyl sebacate; azelaic acid esters such as bis(2-ethylhexyl) azelate; paraffins such as chlorinated paraffin; polypropylene. Examples of suitable oils include glycols such as pyrene glycol and polyethylene glycol; epoxy-modified vegetable oils such as epoxidized soybean oil and epoxidized linseed oil; phosphates such as trioctyl phosphate and triphenyl phosphate; phosphites such as triphenyl phosphite; ester oligomers such as esters of adipic acid and 1,3-butylene glycol; low molecular weight polymers such as low molecular weight polybutene, low molecular weight polyisobutylene, and low molecular weight polyisoprene; and oils such as process oil and naphthenic oil. Among these, glycols such as polypropylene glycol and polyethylene glycol are preferred from the standpoint of availability, ease of handling, and economic efficiency. These may be used alone or in combination of two or more.

[0070] The melt flow rate (MFR) of the rubber-containing acrylic resin composition (A) measured at 220°C and a load of 2.1 kg is preferably 0.1 g / 10 min or more and less than 100 g / 10 min. By setting the MFR within the above range, film formation stability can be obtained. A plasticizer or the like may be added to adjust the MFR.

[0071] From the viewpoints of film formation stability and abrasion resistance, the thickness of the layer made of the resin composition is preferably 3 to 200 μm. The thickness of the layer made of the resin composition is more preferably from 3 to 100 μm, and further preferably from 4 to 70 μm.

[0072] From the viewpoints of film formation stability, abrasion resistance, and decorative moldability, the ratio (r / s) of the thickness (r) of the layer made of the resin composition to the thickness (s) of the substrate is preferably 1 / 30 to 1 / 2, more preferably 1 / 25 to 1 / 3, and even more preferably 1 / 20 to 1 / 4. Moreover, the thickness of the laminated film (total thickness including the thickness of the layer made of the resin composition, the thickness of the base layer, and the thickness of each layer that may be optionally included) is preferably 10 to 300 μm, more preferably 15 to 250 μm, and even more preferably 20 to 200 μm, from the viewpoints of film formation stability and decorative formability.

[0073] From the viewpoint of decorative formability, the laminated film of the present invention has a tensile elongation at 150° C. of preferably 100% or more, more preferably 120% or more, and even more preferably 150% or more. The upper limit is not particularly limited, but is usually 500%. The tensile elongation of the laminated film can be measured using a tensile tester according to a method in accordance with JIS K7161-1-2014.

[0074] The method for producing the laminated film of the present invention is not particularly limited, and for example, a layer made of the resin composition of the present invention and a base layer may be bonded together via an adhesive layer, a melt of the resin composition of the present invention may be extruded onto the base layer and laminated by heat pressing, the resin composition of the present invention and a raw material (e.g., a thermoplastic resin) constituting the base layer may be co-extruded and laminated, or the laminate may be formed by injection molding. Among these, the method of co-extruding the resin composition of the present invention and the raw material constituting the substrate layer (e.g., a thermoplastic resin) is preferred, since it allows the resin composition layer and the substrate layer to be produced in one go, and also allows the production of a wide film.

[0075] <Coating material> The covering material of the present invention is formed using a resin film made of the resin composition of the present invention, or a laminate film of the present invention. The resin film and laminate film of the present invention are excellent in abrasion resistance, weather resistance and decorative moldability, and are therefore suitable for use as various covering materials. As a covering material, it can be used for the exterior and interior of vehicles, the exterior and interior of building materials, top sheets of cards, etc., top sheets of home appliances, etc. EXAMPLES

[0076] The present invention will be explained in more detail below with reference to examples, but the present invention is not limited by these in any way. The raw materials used in the examples and comparative examples are listed below.

[0077] (Polyurethane) Polyurethane 1: Polycarbonate-type thermoplastic polyurethane having an aliphatic diisocyanate component and a hardness of 95A, manufactured by Mitsui Chemicals, Inc., product name "Fortimo XCT-A1095", MFR (220°C) = 2.7g / 10min Polyurethane 2: Polycaprolactone-type thermoplastic polyurethane having an aliphatic diisocyanate component and a hardness of 97A, manufactured by BASF Japan Ltd., product name "Elastollan NY997-10UN", MFR (220°C) = 12g / 10min Polyurethane 3: Polyester-type thermoplastic polyurethane containing an aliphatic diisocyanate component and having a hardness of 90A, manufactured by Fuwafon TPU Co., Ltd., product name "HF-7390A3-3", MFR (220℃) = 1g / 10min Polyurethane 101: Polyether-type thermoplastic polyurethane containing an aliphatic diisocyanate component and having a hardness of 80A, manufactured by BASF Japan Ltd., product name "Elastollan NY88A10", MFR (220℃) = 41g / 10min Polyurethane 102: Polycarbonate + caprolactone type thermoplastic polyurethane containing aromatic diisocyanate components and having a hardness of 97A, manufactured by Dainichi Seika Chemicals Co., Ltd., product name "Rezamin P897", MFR (220℃) = 17g / 10min

[0078] (lubricant) Lubricant 1: Fatty acid amide, manufactured by CRODA, product name "IncroMAX PS" Lubricant 2: Fatty acid ester, manufactured by CRODA, product name "IncroMAX100"

[0079] (others) Coating agent: Urethane-based self-repairing coating agent, manufactured by Arakawa Chemical Industries, product name "Aracoat SH300"

[0080] Acrylic resin composition (A1a): A rubber-containing acrylic resin composition (A1a) obtained by the following method was used.

[0081] <Production Example 1: Production of Core-Shell Rubber (A1-1a)> A core-shell rubber (A1-1a) was obtained in the same manner as for the acrylic rubber particles (A-1B) in Production Example 2 of WO 2014 / 192708.

[0082] <Production Example 2: Production of Thermoplastic Polymer (A1-2a)> A thermoplastic polymer (A1-2a) was obtained in the same manner as in Production Example 5 of WO 2014 / 192708.

[0083] <Production Example 3: Production of rubber-containing acrylic resin composition (A1a)> The core-shell rubber (A1-1a) and thermoplastic polymer (A1-2a) obtained in Production Examples 1 and 2, and additives were mixed in the ratios shown in Table 1 using a Henschel mixer, and the mixture was melt-kneaded using a 35 mm diameter screw-type twin-screw extruder (L / D=26) under conditions of a cylinder temperature of 200°C to 240°C and a die temperature of 240°C, and pelletized to obtain a rubber-containing acrylic resin composition (A1a).

[0084] The details of the additives shown in Table 1 are as follows. PEG: Polyethylene glycol, Sanyo Chemical Industries, Ltd., product name "PEG20000" LA-31: ADEKA Corporation, product name "ADEKA STAB LA-31RG" TV234: BASF, product name "Tinuvin234" C2020: BASF, product name "Chimassorb2020" Irg1076: BASF, product name "Irganox1076"

[0085] The tan δ peak temperature of the obtained rubber-containing acrylic resin composition (A1a) was −35° C. on the low temperature side and 103° C. on the high temperature side.

[0086] [Table 1]

[0087] <Physical properties of raw materials> The hardness, MFR (melt flow rate), glass transition temperature (Tg) and melting point (Tm) of Polyurethanes 1 to 3 and 101 to 102, and the melting point (Tm) of the lubricant were measured by the following methods.

[0088] 1.Hardness The hardness (A hardness) of the polyurethane was measured according to JIS K 7311-1995 (Testing method for polyurethane thermoplastic elastomers).

[0089] 2.MFR The MFR of polyurethane was measured under conditions of a temperature of 220°C and a load of 2.16 kg in accordance with JIS K7210-1999.

[0090] 3. Glass transition temperature (Tg) and melting point (Tm) The polyurethane was heated at a rate of 10° C. / min using a differential scanning calorimeter manufactured by PerkinElmer, Inc., under the trade name "DSC8000," to measure the Tg and Tm of the polyurethane.

[0091] <Preparation of resin film> [Examples 1 to 6, Comparative Examples 1 to 2] Polyurethane and a lubricant were melt-kneaded to prepare a resin composition in the composition shown in Tables 2 and 3, and the molten resin was extruded to produce a resin film having a thickness shown in Tables 2 and 3. In Comparative Example 1, no lubricant was used, and polyurethane 1 was melt-extruded to produce a resin film having a thickness shown in Table 3.

[0092] <Manufacturing of laminated film> [Examples 7 and 8] A resin composition was prepared by melt-kneading polyurethane and a lubricant in the composition shown in the "Layer I" column of Table 4, and co-extruded with the acrylic resin composition (A1a) that is the raw material for Layer II to produce a laminate film with the thickness ratio shown in Table 4.

[0093] Comparative Example 3 A coating agent having a thickness shown in Table 4 was applied onto Layer II having a thickness shown in Table 4 to produce a laminate film.

[0094] Comparative Example 4 A film made of polyurethane 102 was produced with the composition shown in Table 4. The film of Comparative Example 4 was a single layer film.

[0095] <Evaluation of resin films and laminated films> The resin film and laminate film were evaluated as follows, and the evaluation results are shown in Tables 2 to 4. The evaluation results with "-" indicate that no data was available because no measurement was performed, or that no calculations could be performed because no measurement data was available.

[0096] 1.Weather resistance evaluation 1-1. Moisture and heat resistance The moist heat resistance was evaluated for the resin films of Examples 1 to 6 and Comparative Examples 1 and 2, and the laminated films of Examples 7 and 8. The moist heat resistance was evaluated based on the results of (1) and (2) below, and according to the evaluation criteria shown in (3).

[0097] (1) Appearance evaluation The surface of the resin film and the surface of the layer I side of the laminate film were visually observed and evaluated according to the following criteria ("Before storage" in Tables 2 to 4). In addition, the resin film and the laminate film were stored in an environment of 40°C and 90% RH for one month, and then evaluated again according to the following criteria ("After storage at 40°C and 90% RH" in Tables 2 to 4). ◯ (good): The surface is transparent with no powdering, bleeding or color unevenness. × (poor): Powdering, bleeding or color unevenness is observed on the surface.

[0098] (2) Light transmittance and haze Using Nippon Denshoku Industries Co., Ltd.'s product name "NDH 5000", the resin film surface and the I-layer side surface of the laminated film were irradiated with light, and the light transmittance and haze were measured in accordance with JIS K-7136 ("Before storage" in Tables 2 to 4). In addition, the resin film and the laminated film were stored in an environment of 40°C and 90% RH for one month, and the light transmittance and haze were measured again ("After storage at 40°C and 90% RH" in Tables 2 to 4). Furthermore, from the data obtained above, the change in haze before and after storage "Δhaze (after storage at 40°C and 90% RH - before storage)" was calculated. Regarding light transmittance, a value of over 91% both before and after storage was deemed to have passed the test. Regarding haze, a sample with a change in haze between before and after storage within ±2 was rated as passing.

[0099] (3) Moisture and heat resistance evaluation The moist heat resistance of the resin film and the laminated film was evaluated according to the following criteria. ◯ (good): Appearance evaluation is ◯ both "before storage" and "after storage at 40° C. and 90% RH", light transmittance is 91% or more, and the change in haze before and after storage is within ±2. × (poor): Either "before storage" or "after storage at 40°C and 90% RH", the appearance evaluation was ×, the light transmittance was 91% or less, or the change in haze before and after storage exceeded ±2.

[0100] 1-2.Yellowing resistance The laminated film of Example 7 and the film of Comparative Example 4 were evaluated for yellowing resistance. ·Device Suga Testing Machine, 7.5kW, product name "Super Xenon Weather Meter SX75" Testing standards ISO4892-2 methodA ·Equipment conditions: Xenon lamp (7.5kW), inner filter (quartz), outer filter (#275)

[0101] Test conditions The combined two hours of the following (1) and (2) constituted one cycle, and the yellowing degree (YI value; yellow index value) was measured after 1000 hours and at the initial time. (1) Irradiation BPT (black panel temperature) 63℃, humidity 50%RH, illuminance 60W / m 2 , time 1h42m (2) Irradiation + Rain Temperature 38℃, humidity 95%RH, illuminance 60W / m 2 , time 18m

[0102] ·evaluation The evaluation was based on the following criteria. ○ (good): YI value is 5 or less both "before the test" and "after the test". × (poor): YI value exceeds 5 either "before test" or "after test".

[0103] 2. Wear resistance evaluation 2-1. Coefficient of kinetic friction The dynamic friction coefficients of the resin films of Examples 1 to 6 and Comparative Examples 1 and 2, and the laminate films of Examples 7 to 8 and Comparative Example 3 were measured using a product name "TL201Tt" manufactured by Traniity Lab under the conditions of a load of 200 g, a speed of 50 mm / sec, a travel distance of 50 mm, and cotton as the counter material. The coefficient of dynamic friction was rated as acceptable if it was 0.450 or less.

[0104] 2-2. Abrasion resistance before storage The resin films of Examples 1 to 6 and Comparative Examples 1 and 2, and the laminate films of Examples 7 to 8 and Comparative Example 3 were evaluated for abrasion resistance before storage (immediately after production). The resin film surface and the I-layer surface of the laminate film were rubbed 100 times with 1.96 N, 20 mm wide, #0000 steel wool (rubbing test), and the haze after this was measured in the same manner as in 1-1.(2) above ("after 100 steel wool rubs" in Tables 2 to 4). The difference from the haze measured in 1-1.(2) above ("before test" in Tables 2 to 4) "Δhaze (after 100 rubs - before test)" was calculated and evaluated according to the following criteria. ○ (good): “Δhaze (after 100 strokes – before test)” is within ±2. × (poor): “Δhaze (after 100 strokes – before test)” exceeds ±2.

[0105] 2-3. Abrasion resistance after storage at 40℃ 90% RH The resin films of Examples 1 to 6 and the laminated films of Examples 7 to 8 were stored for one month in an environment of 40°C and 90% RH, and then subjected to the same abrasion test as in 2-2. above, and the abrasion resistance was evaluated using the same criteria as in 2-2. above.

[0106] 3.Decorative moldability evaluation The decorative formability was evaluated from the viewpoints of (1) stretchability and (2) transparency after stretching for the resin films of Example 1, Example 6, and Comparative Example 1, and the laminate films of Examples 7 to 8, and Comparative Example 3. When the evaluation results of (1) and (2) were both ◯, the resin film or laminate film had excellent decorative formability.

[0107] (1) Stretchability The resin film and laminate film were cut into strips (test pieces: width 10 mm, initial length 40 mm) and tensile tests were performed in the MD direction (machine direction) and TD direction (direction perpendicular to the machine direction (including the range approximately perpendicular)); transverse direction) using a tensile tester (Shimadzu universal testing machine AG-XPlus) at an atmosphere of 150°C and a tensile speed of 100 mm / min. The breaking elongation was measured and evaluated according to the following criteria. [Evaluation of Resin Film] ◯ (good): The tensile elongation at break in both the MD and TD directions is 100% or more. × (poor): The tensile elongation at break in the MD or TD direction is less than 100%. [Evaluation of Laminated Film] ◯ (good): The tensile elongation at break in both the MD and TD directions is 100% or more, and there is no delamination. × (poor): The tensile elongation at break in the MD or TD direction is less than 100%, or delamination has occurred.

[0108] (2) Transparency after stretching To evaluate the transparency after stretching, resin films and laminate films with a width of 50 mm and an initial length of 40 mm were stretched to a tensile elongation of 300% in the MD direction at a tensile speed of 100 mm / min in an atmosphere of 150°C using a tensile testing machine (Shimadzu universal testing machine AG-XPlus) to obtain samples for measurement. In addition, the appearance of the resin film and the laminated film after the tensile test was observed. The transparency after stretching was evaluated based on the haze and appearance according to the following criteria. [Evaluation of Resin Film] ◯ (good): The haze after stretching is 5 or less, and the film has a transparent appearance without whitening. × (poor): The haze after stretching exceeds 5, or whitening occurs in the film. [Evaluation of Laminated Film] ◯ (good): The appearance of the film after stretching is transparent, and no whitening occurs. × (poor): Whitening occurred in the film after stretching.

[0109] [Table 2]

[0110] [Table 3]

[0111] [Table 4]

[0112] The following can be seen from Tables 2 to 4.

[0113] [Weather resistance] The resin films of Examples 1 to 6 had good moist heat resistance because the thermoplastic polyurethane had a hardness of 90 A or more. On the other hand, the resin film of Comparative Example 2 had a thermoplastic polyurethane hardness of less than 90 A, so that it became powdery after storage at 40°C and 90% RH for one month, and had poor moist heat resistance. In addition, the laminated film of Example 7 had excellent yellowing resistance because the thermoplastic polyurethane contained an aliphatic diisocyanate component, whereas the film of Comparative Example 4 had poor yellowing resistance because the thermoplastic polyurethane contained an aromatic diisocyanate component.

[0114] [Wear resistance] The resin films of Examples 1 to 6 and the laminate films of Examples 7 to 8 had a thermoplastic polyurethane hardness of 90A or more and contained a lubricant, so that the dynamic friction coefficient was small and the abrasion resistance was good. These resin films and laminate films had good abrasion resistance even after being stored at 40°C and 90% RH for one month, and were found to have excellent abrasion resistance even when placed in high temperature and high humidity environments such as the exterior and interior of vehicles and building materials, and the top sheets of home appliances. On the other hand, the resin film of Comparative Example 1 had a large dynamic friction coefficient and poor abrasion resistance because it did not contain a lubricant, and the resin film of Comparative Example 2 had a large dynamic friction coefficient and poor abrasion resistance because the hardness of the thermoplastic polyurethane was less than 90A.

[0115] [Decorative moldability] The resin films of Examples 1 and 6 had good stretchability and transparency after stretching, and also had good decorative formability. Moreover, the laminated films of Examples 7 and 8 had good stretchability and transparency after stretching, did not undergo delamination between the resin composition layer (layer I) and the acrylic resin layer (layer II), and had good decorative formability. On the other hand, the laminated film of Comparative Example 3 had poor stretchability, and delamination occurred between the coating layer (layer I) and the acrylic resin layer (layer II), resulting in poor decorative formability.

[0116] As described above, the resin composition of the present invention contains a thermoplastic polyurethane having an aliphatic diisocyanate component and a hardness of 90A or more, and a lubricant, and does not contain silica or contains silica in a ratio of less than 5 parts by mass per 100 parts by mass of the thermoplastic polyurethane, so that it is possible to provide a resin film, a laminated film, and a coating material that have excellent weather resistance, abrasion resistance, and decorative formability.

Claims

1. A resin composition comprising a thermoplastic polyurethane having a molecular skeleton derived from an aliphatic diisocyanate in the molecule and having a hardness of 90A or more, the thermoplastic polyurethane including one or more selected from the group consisting of a polycarbonate type, a polycaprolactone type, and a polyester type, and a lubricant including one or more selected from the group consisting of a fatty acid amide and a fatty acid ester.

2. 2. The resin composition according to claim 1, wherein the content of the lubricant is 0.01 to 2.0 parts by mass based on 100 parts by mass of the thermoplastic polyurethane.

3. 3. The resin composition according to claim 1, wherein the thermoplastic polyurethane has a glass transition temperature of 30° C. or lower.

4. The resin composition according to any one of claims 1 to 3, wherein the thermoplastic polyurethane has a melt flow rate at 220°C of 0.1 g / 10 min or more.

5. The resin composition according to any one of claims 1 to 4, wherein the melting point of the lubricant is 25°C or higher.

6. A resin film comprising the resin composition according to any one of claims 1 to 5, and having a dynamic friction coefficient of 0.450 or less.

7. A resin film comprising the resin composition according to any one of claims 1 to 5, and having a tensile elongation at 150°C of 100% or more.

8. A resin film comprising the resin composition described in any one of claims 1 to 5 and having a light transmittance of 90% or more.

9. A resin film comprising the resin composition according to any one of claims 1 to 5, and having a haze of 10% or less.

10. A coating material using the resin film according to any one of claims 6 to 9.

11. A laminated film having a layer made of the resin composition according to any one of claims 1 to 5 and a substrate layer.

12. The laminate film according to claim 11, wherein the layer made of the resin composition has a thickness of 3 to 200 μm.

13. 13. The laminated film according to claim 11, which has a tensile elongation at 150°C of 100% or more.

14. A coating material using the laminated film according to any one of claims 11 to 13.

Citation Information

Patent Citations

  • Thermoplastic polyurethane resin composition for calender holding and film / sheetlike material

    JP2001115008A

  • Golf ball

    JP2002336382A

  • Thermoplastic polyurethane resin composition and moisture permeable film

    JP2007217678A

  • Thermoplastic resin composition

    JP2009084526A

  • Active energy ray-curable resin composition

    JP2010053357A